The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1590/psicodrama.v30.606_pt
|View full text |Cite
|
Sign up to set email alerts
|

A Barreira Linguística Como Parte Das Políticas Editoriais De Diversidade E Inclusão

Abstract: Na publicação científica, assim como na sociedade em geral, o papel do viés intencional e não intencional tem merecido crescente atenção. Preconceitos baseados em etnia, gênero, religião, deficiência, educação, ambiente institucional, status de carreira, orientação sexual, idioma etc. têm sido uma preocupação para os editores científicos. Esse viés pode se manifestar

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The importance of our results is that they shed light on the role of language in bilingual search activities. Specifically, these findings are a promising response to authoritative academics' (Amano et al, 2023;Fleury and Heredia, 2022;Nuñez and Amano, 2021;Piller et al, 2022;Ransing et al, 2023;Zenni et al, 2023) call for more actions concerned with multilingual search literature that counter the English-only (and English-always) format. Although we hypothesized that posts in English would result in a lower level of performance than those in the students' first language, it is encouraging to report here that our results indicate that students can be With respect to RQ2, one out of the four demographic variables analyzed seemed to predict students' performance.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…The importance of our results is that they shed light on the role of language in bilingual search activities. Specifically, these findings are a promising response to authoritative academics' (Amano et al, 2023;Fleury and Heredia, 2022;Nuñez and Amano, 2021;Piller et al, 2022;Ransing et al, 2023;Zenni et al, 2023) call for more actions concerned with multilingual search literature that counter the English-only (and English-always) format. Although we hypothesized that posts in English would result in a lower level of performance than those in the students' first language, it is encouraging to report here that our results indicate that students can be With respect to RQ2, one out of the four demographic variables analyzed seemed to predict students' performance.…”
Section: Resultsmentioning
confidence: 89%
“…Hence, the factors that influence undergraduate students’ ability to seek online bilingual scientific information are unknown. This gap in the literature should be addressed as there is a chorus of authoritative voices (Fleury and Heredia, 2022; Piller et al , 2022; Singh and Lu, 2020; Zenni et al , 2023), calling for concrete actions concerned with bi/multilingual knowledge exchange practices that counter the English-only (and English-always) format. Fleury and Heredia (2022), for instance, claim that scientific research practices should be multilingual since science progresses when scientists work in collaborative and international ways.…”
Section: Rationale Of the Contextual Factors Examined In The Present ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding equity, it is observed that it involves a sense of justice, a value for impartial conduct that allows a guarantee of rights regarding access to education and quality employment with adequate remuneration and housing [18]. As for inclusion, whether in society or in higher education, in Brazil, it is regulated by four legal documents: 1.…”
Section: Introductionmentioning
confidence: 99%
“…The individual is born with male/female genitalia, but cannot psychologically fit in with this fact, that is, as male, he perceives himself as female, if female, he perceives himself as male[15] 17. A pathology in terms of identity disorder, in the face of non-conformity between sex and gender[126] 18. Greater ABC, involves seven municipalities in São Paulo: Santo André, São Bernardo do Campo, São Caetano do Sul, Diadema, Mauá, Ribeirão Pires and Rio Grande da Serra.…”
mentioning
confidence: 99%